2013
DOI: 10.1186/1476-7120-11-26
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of exercise stress echocardiography in the treadmill with upright evaluation during and after exercise

Abstract: Exercise stress echocardiography is the most frequently used stress test in our laboratory. Exercise echocardiography is used mainly in the study of patients with coronary artery disease. However, the technique is increasingly being used to study other diseases.In our centre, we use an original methodology, published by us in 2000, in which we evaluate heart function during exercise in the treadmill. After the exercise, patients are maintained in orthostatic position when appropriate or lying down in left late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 74 publications
(85 reference statements)
0
13
0
Order By: Relevance
“…Exercise stress echocardiography is perhaps the best method to evaluate cardiac function during exercise, as it provides information on many parameters, including pulmonary pressures, diastolic and systolic function, gradients across heart valves and ischaemia. 185…”
Section: Exercise Training For Patients With T2dm and Cardiovascular mentioning
confidence: 99%
“…Exercise stress echocardiography is perhaps the best method to evaluate cardiac function during exercise, as it provides information on many parameters, including pulmonary pressures, diastolic and systolic function, gradients across heart valves and ischaemia. 185…”
Section: Exercise Training For Patients With T2dm and Cardiovascular mentioning
confidence: 99%
“…Also, as mentioned in the previous studies [26, 27], intramuscular mechanoreceptors activated through LBPP might have attenuated the acute change in blood perfusion. Reduced blood perfusion might imply risk as less blood flow could induce dizziness [18]. However, considering the fact that cerebral artery velocity and cardiac output are less likely to be affected [28, 29] it could be suggested that LBPP has little or no adverse effects due to fluctuations in the cardiovascular response.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear whether blood flow alteration occurs during LBPP walking, and there is limited evidence on this [17]. Given that fluctuation of blood flow could result in dizziness or ischemia in head and upper body, which might impair safety of gait practice [18], understanding the effects of LBPP on blood perfusion could be advantageous for patients undergoing orthopedic rehabilitation using LBPP treadmill.…”
Section: Introductionmentioning
confidence: 99%
“…At least in some centers two-dimensional stress echocardiography is performed in the standing position throughout the exercise stress test with image acquisition at peak exercise [2]. Standing position, both at rest and during exercise, is a normal and fundamental activity of daily life, but may precipitate an unexpected fall in cardiac patients predisposed to syncope, especially in patients with unsuspected aortic or sub-aortic obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Stress echocardiography has been introduced many years ago as a valuable method in the detection of myocardial ischemia in patients with known or suspected coronary artery disease by assessing wall motion abnormalities [ 1 ]. At least in some centers two-dimensional stress echocardiography is performed in the standing position throughout the exercise stress test with image acquisition at peak exercise [ 2 ]. Standing position, both at rest and during exercise, is a normal and fundamental activity of daily life, but may precipitate an unexpected fall in cardiac patients predisposed to syncope, especially in patients with unsuspected aortic or sub-aortic obstruction.…”
Section: Introductionmentioning
confidence: 99%